Magnitude of self-harm and associated factors among postnatal mothers attending immunization clinics at public health facilities in Boneya Boshe Woreda, Western Ethiopia, 2023: institution-based cross-sectional study design - Wedajo, Lema Fikadu; Hajure, Mohammedamin; Abdu, Zakir; Tesfaye, Gebremeskel Mulatu; Workneh, Yadeta Alemayehu; Gezimu, Wubishet; Hussen, Mustefa Adem; Gemeda, Aman Dule; Teferi, Sheleme Mengistu; Alemu, Solomon Seyife (Frontiers in Public Health, 2024)
Background: Self-harm is a preventable leading cause of maternal morbidity and mortality all over the world, with a significant impact on health care systems.Objective: To assess the magnitude of self-harm and associated factors among postnatal mothers attending immunization clinics.Method: An institution-based cross-sectional study was employed among postnatal mothers attending infant immunization clinics at public health facilities in Boneya Boshe Woreda, Western Ethiopia, from October 1-30, 2023. A pretested, face-to-face interviewer-administered structured questionnaire prepared by Kobo Toolbox was used to collect the data. Both bi-variable and multi-variable logistic regression analyses were done. The level of significance was declared at P-value < 0.05 with a 95% CI.Results: Among 423, 415 mothers participated in the study, for a response rate of 98.10%. The magnitude of self-harm was 12.53% (95% CI: 9.33, 15.73). Husband involvement in maternity and child health care (AOR = 1.90; 95% CI: 1.12, 2.10), depression (AOR = 2.79; 95% CI: 2.14, 6.94), loneliness (AOR = 2.49; 95% CI: 1.15, 5.40), postpartum intimate partner violence (AOR = 2.15; 95% CI: 1.01, 4.54), average monthly income (AOR = 3.70; 95% CI: 2.17, 10.50), and postnatal care (AOR = 2.72; 95% CI: 1.28, 5.80) were significantly associated factors.The study sought a magnitude of self-harm that was slightly higher than the previous study conducted in the northern part of Ethiopia. Therefore, health care providers should focus on identified factors during postnatal care to overcome them.Similarly, the concerned body should develop an effective strategy based on identified factors to pay attention to postnatal mothers.